Analisis Penerapan Prinsip-prinsip Islamic Good Corporate Governance (GCG) pada Pengelolaan Keuangan Syariah di Baznas: Studi Kasus Baznas Kabupaten Morowali - Lalu Khaeril Anwar; Iwan Setiadi; Pitri Yandri; Mukhaer Pakkanna; Amie Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Analysis of the Implementation of Islamic Good Corporate Governance (GCG) Principles in Sharia Financial Management at BAZNAS (A Case Study of BAZNAS Morowali Regency). This research aims to analyze the application of Islamic Good Corporate Governance (GCG) principles in the management of sharia finance at the National Zakat Agency (BAZNAS) in Morowali Regency. Islamic GCG is a governance principle founded on Islamic values, including syura (consultation), amanah (responsibility), justice, and transparency. The study used a qualitative approach with a case study method, where data was collected through in-depth interviews, observation, and documentation. The informants were BAZNAS leaders. The results show that the implementation of Islamic GCG principles at BAZNAS Morowali Regency is progressing quite well, particularly in the areas of financial reporting transparency, accountability in the use of zakat funds, and strict sharia supervision. However, some challenges still exist, such as a limited number of human resources who fully understand Islamic governance principles and difficulties in the digitalization of financial reporting. This research contributes to the literature on sharia financial governance and provides recommendations for strengthening a governance system that aligns with Islamic values within zakat management institutions. By optimally implementing Islamic GCG, BAZNAS is expected to increase public trust and more effectively and equitably distribute zakat funds to recipients (mustahik).